- VACCINATION STATUS AND THE SEVERITY OF COVID-19 PATIENTS - Mugi Hartoyo; Budiyati Budiyati; Riskiyana Sukandhi Putra; Tajudin Hudaiby Nizar (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Introduction: On January 30, 2020, the SARS-CoV-2 outbreak was a public health emergency of international concern. At the end of 2022 there was still the spread of COVID-19 even though the pandemic status had changed to endemic. One of the efforts to reduce the risk of being infected with COVID-19 is the provision of vaccines to the community. However, previous studies have shown that some people who have been vaccinated still have confirmed COVID-19 with varying severity and symptoms. The purpose of the study was to determine the relationship between vaccination status and the severity of COVID-19. Method: This quantitative research with a retrospective cohort study was applied to 92 COVID-19 patients at a secondary hospital in Purbalingga, Central Java, Indonesia recruited by proportional simple random sampling technique. The data were collected from the medical records of COVID-19 patients from May to August 2021. The severity and symptoms of COVID-19 were determined based on the guidelines of the National Institutes of Health which include asymptomatic infection, mild symptoms, moderate symptoms, severe symptoms, and critical. The collected data were analyzed using the Fisher’s Exact test. Results: Of the 92 respondents, there were 49 (53.35%) male patients and the most comorbid was diabetes mellitus with a total of 28 (30.4%) patients. Respondents who have not been vaccinated are 64 (69.6%) patients. Patients with a high severity level of COVID-19 were more frequently found among respondents who had not been vaccinated, 54 (58.7%). There is a relationship between vaccination status and the severity of COVID-19 (p = 0.000). The public is advised to complete the vaccine status that has been facilitated by the government. Conclusion: Vaccination potentially reduces the severity of COVID-19.